(untitled) (Journal of Asian Development Studies, 2024)
Corporate Social Responsibility (CSR) is a fascinating topic since it is an essential element of the business’s strategy for increasing its worth from the perspective of investors. This study aims to examine the impact of corporate social responsibility on tax avoidance with the moderating roleof business strategy in the context of Pakistan. The CSR spending ratio measures CSR, while tax avoidance is measured by GAAP ETR from 2016 to 2020. Data for this study was acquired from the Pakistan Stock Exchange (PSX), 120 listed nonfinancial firms. Inthis study, tax avoidance is the dependent variable, while CRS is the independent variable. Firm size, performance, leverage, dividend payout ratio, capital expenditure, and sales growth are all control variables for analyzingtax avoidance. The moderating variable in this study was businessstrategy, which has been utilizedto assess the association between CRS and tax avoidance. Regression results of the random effect model (REM) show a significant positive relationship between the CSR spending ratio andtax payments at 10%, fixed effect model (FEM) at 5%, and generalized methods of moments (GMM) estimation at 1% level of significance respectively, indicating that firms with higher CSR spending are more likely to carry out tax payment activities. The findings also show a negative and significant (FEM and GMM at 5%, REM at 1%) relationship between business strategy and tax payment in non-financial firms listed on the PSX, indicating a positive relationship between business strategy and tax avoidance. The study examined that CSR and profitability have a positive impact on tax avoidance, whereas board size, leverage, and dividend payout ratio has an inverse relationship to tax avoidance. This study also explored that business strategy has positive moderates with the association of CRS and tax avoidance in the context of Pakistan